EXPERIENCE OF FOREIGN COUNTRIES IN MANAGEMENT OF CONSTRUCTION MATERIALS MANUFACTURING ENTERPRISES AND OPPORTUNITIES TO USE THEM (Marketing Journal, 2025)
This study is focused on exploring ways to improve management efficiency in construction materials manufacturing enterprises. The analysis thoroughly examines the role of quality management systems in ensuring process discipline, the advantages of digital transformation in real -time monitoring of production processes, as well as the importance of energy efficiency and environmental management for sustainable development. The conclusions, developed based on international experience, provide essential practic al recommendations for optimizing enterprise operations, ensuring efficient use of resources, and aligning activities with international standards.
Keywords: quality management; digital transformation; energy efficiency; environmental management; construction materials industry. 197